Pengaruh Persepsi Harga Dan Promosi Terhadap Keputusan Pembelian : (Survei Pada Konsumen Perusahaan Kacang Telor Bebe Di Kota Tasikmalaya) - Muhammad Rifaz Rifaldi (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine and analyze the effect of price perception and promotion on purchasing decisions at the Kacang Telor Bebe Company. The research method used in this study is quantitative research with a population survey approach. In this study, the purchase decision was made with a sampling method using accidental sampling, which obtained a sample of 100 people. The technique used in this research is multiple linear regression. The results of data analysis show that price perception and promotion have a significant effect simultaneously and partially on competitive advantage in the Kacang Telor Bebe Company. Therefore, the Peanut Telor Bebe Company must make adjustments to Price Perceptions and increase Promotions so as to create a significant Purchase Decision.